2006
DOI: 10.1007/s00203-006-0205-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of putative ancestors of the multidrug-resistant Salmonella enterica serovar typhimurium DT104 clone harboring the Salmonella genomic island 1

Abstract: The origin of multidrug-resistant Salmonella enterica serovar typhimurium (S. typhimurium) harboring the Salmonella Genomic Island 1 (SGI1), which was detected for the first time in the mid-1980s is unknown. In this study, we performed microarray genomotyping of four multidrug-resistant SGI1 positive strains and found that unlike the S. typhimurium LT2 strain, the multidrug-resistant strains lacked genes STM0517-0529 allowing the utilization of allantoin as a sole nitrogen source. We extended this observation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 32 publications
4
27
0
Order By: Relevance
“…Recent population studies are supporting the notion that the prophage content is one the most dynamic part of the genome, indicating that phage integration/excision are frequent events shaping Salmonella genome evolution (Hermans et al, 2006;Cooke et al, 2007;Drahovska et al, 2007;Matiasovicova et al, 2007;Cooke et al, 2008;Litrup et al, 2010). These observations are in agreement with the phage remnants found in the genomes of Salmonella (McClelland et al, 2001;Parkhill et al, 2001;Porwollik et al, 2002;Chan et al, 2003;Porwollik and McClelland 2003;Matiasovicova et al, 2007).…”
Section: Phagesupporting
confidence: 52%
“…Recent population studies are supporting the notion that the prophage content is one the most dynamic part of the genome, indicating that phage integration/excision are frequent events shaping Salmonella genome evolution (Hermans et al, 2006;Cooke et al, 2007;Drahovska et al, 2007;Matiasovicova et al, 2007;Cooke et al, 2008;Litrup et al, 2010). These observations are in agreement with the phage remnants found in the genomes of Salmonella (McClelland et al, 2001;Parkhill et al, 2001;Porwollik et al, 2002;Chan et al, 2003;Porwollik and McClelland 2003;Matiasovicova et al, 2007).…”
Section: Phagesupporting
confidence: 52%
“…When we analysed genomes of three S. Typhimurium strains, we found that almost all of the variation in their XbaI-generated PFGE profiles could be attributed to the presence of prophages. The fact that prophages are major sources of genomic variation in different S. Typhimurium strains has been shown by several studies using microarray genomotyping (Porwollik et al, 2004;Reen et al, 2005;Matiasovicova et al, 2007); these studies have indicated that Fels1 and Fels2 prophages are relatively specific for the LT2 strain. Other studies, using conventional PCR, have found that sopE, encoded by a Fels-like prophage, is quite uncommon to S. Typhimurium (Mirold et al, 1999).…”
Section: Discussionmentioning
confidence: 96%
“…This information has led to studies that have used the detection of prophage sequences for strain characterization (Mikasova et al, 2005;Hermans et al, 2005;Ross & Heuzenroeder, 2005); however, the approach in those studies was rather arbitrary. In this study, we used accumulated genomic data, either from genome sequencing (McClelland et al, 2001) or from microarray genomotyping (Porwollik et al, 2004;Reen et al, 2005;Matiasovicova et al, 2007), for rational design of a PCRtyping system based on the presence or absence of mobile DNA sequences. Multiplexing of the specific PCR further simplified the protocol, and made it user friendly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations